Nanostar morphology of plasmonic particles strongly enhances photoelectrochemical water splitting of TiO2 nanorods with superior incident photon-to-current conversion efficiency in visible/near-infrared region. (10th January 2018) - Wang, Lingyun; Wang, Yu; Schmuki, Patrik; Kment, Stepan; Zboril, Radek
Abstract: Photoelectrochemical (PEC) water splitting with TiO2 photoanodes is a promising technique for converting solar energy into a clean chemical energy. The key drawbacks of titania involve still a low PEC performance and its large band gap energy allowing absorption only in the UVregion. Plasmonic nanostructures such as Au and Ag represent a powerful tool towards the light harvesting enhancement with the efficiency dependent on their size and loading. Here, the unique nanostar morphology of plasmonic particles is presented as a new principal factor allowing the significant improvement of the incident photon-to-current conversion efficiency (IPCE) and the extension of light absorption over the broadband UV–Vis–NIR region. A plasmonic metal/semiconductor heterostructure synthesis is based on ex situ deposition of multispiked gold nanostars (Au-NSs) onto hydrothermally grown TiO2 nanorods. Compared to bare TiO2 nanorods, the Au-NSs-decorated TiO2 exhibits 350% and ca. 20% increase in the photocurrent density under visible light and simulated sunlight irradiation, respectively. Importantly, a significant enhancement of IPCE over the Vis-NIR region is observed with single-phase Au-NSs, the value two times higher compared to the spherical morphology. This is largely attributed to the long-wavelength plasmon resonances of Au-NSs and their ability to promote surface plasmon resonance (SPR)-mediated hot electron transfer. Graphical abstract: Highlights: A synthetic approach to grow Au nanostars (NSs) on TiO2 nanorods (NRs) was developed. By attaching the Au NSs to TiO2 NRs the absorption over Vis-NIR region is obtained. The multispike Au NSs morphology is crucial to enhance IPCE in the Vis-NIR region. Mild thermal treatment of Au NSs/TiO2 NRs significantly improved Schottky contact.